Social Inequalities: Media Approaches and Society Expectations - Berezhnaia, Marina Aleksandrovna; Korkonosenko, Sergey Grigorievich (International Review of Management and Marketing, 2015)
The article deals with the ways of media coverage of financial and ethnic distinctions in society. Analysis is based on the comparative Russian-Swedish research of regional media. The research revealed that material divides are mostly covered through several discourses: social policies aimed at elimination of material differences, information on individual solutions for financial problems, mass media as the helpline for the underprivileged. The audience in Russia finds the coverage of these problems unsatisfactory as it does not touch the structural material divides. The “disparity” discourse was apparent in discussions of ethnic divides and migration. Media also do not present ethnic differences as inequalities; they are either built into the overall context of material divides or placed into “us and they” discourse. Keywords: social inequality, regional media, public, dissonance, discourse. JEL Classifications: H75; I38; J18; Z1; Z13; Z18